2023
DOI: 10.1039/d3cp00540b
|View full text |Cite
|
Sign up to set email alerts
|

Design principles for a nanoconfined enzyme cascade electrode via reaction–diffusion modelling

Abstract: The study of enzymes by direct electrochemistry has been extended to enzyme cascades, with a key development being the ‘electrochemical leaf’: an electroactive enzyme is immobilized within a porous electrode,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Such an observation implies that the mass transport of inhibitor in the bulk solution to enzyme molecules deeply buried in the electrode is not rate‐limiting. This proposal is supported by a recent computational study [35] which concluded that small molecules are able to permeate the ITO layer rapidly and homogeneously, i.e., diffusion within the electrode should not be rate‐limiting when the reaction of interest is sufficiently slow (see Supporting Information for extended discussion). These results thus provide compelling evidence that, for this example at least, the inherent reactivity of enzyme molecules that are highly concentrated in a nanoconfined environment may not differ significantly from that observed in very dilute solution.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Such an observation implies that the mass transport of inhibitor in the bulk solution to enzyme molecules deeply buried in the electrode is not rate‐limiting. This proposal is supported by a recent computational study [35] which concluded that small molecules are able to permeate the ITO layer rapidly and homogeneously, i.e., diffusion within the electrode should not be rate‐limiting when the reaction of interest is sufficiently slow (see Supporting Information for extended discussion). These results thus provide compelling evidence that, for this example at least, the inherent reactivity of enzyme molecules that are highly concentrated in a nanoconfined environment may not differ significantly from that observed in very dilute solution.…”
Section: Discussionmentioning
confidence: 67%
“…The ability to analyse low inhibitor levels in this straightforward way is possible because, although the local concentration of IDH1 R132H in the nanopores is high, the total amount present (around 17 pmoles) [8] is much less than the total amount of inhibitor in the bulk solution “reservoir” (0.4–80 nmoles in these experiments). Transport of small molecules within the ITO layer is not a limiting factor except for very fast reactions [35] . The inhibitor concentration thus remains effectively constant throughout the measurement and pseudo first‐order conditions apply.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a computational paper on the merits of nanoconfinement of enzymes, it was concluded that nanoconfinement was a ‘misleading’ term after modelling only the case of E1 confined alone in which the enzyme electrocatalytically converted NADP(H) presented as a reactant contained in (and arriving from) the bulk solution. The authors ignored the fact that NADP(H) is an exchangeable cofactor that is rapidly recycled during catalysis—it is not a reactant that is consumed 48 , and the second enzyme E2 must be present (making up the minimal pair) together with its substrates 56 . As shown in the next section, the nanoconfinement advantage is obtained only if E1 is coupled to E2 by local NADP(H) recycling—nanoconfinement limits the escape of cofactor and subsequent intermediates during the sequence of reactions.…”
Section: Misunderstandingsmentioning
confidence: 99%
“…The observation that NADP(H) recycling is highly localised raised the question of how effectively reactants (usually smaller than the cofactor) present in solution can reach the large proportion of the enzymes that must be deeply buried in the ITO layer. A computational study showed that although diffusion of small-molecule substrates is retarded when they have to pass through small channels, catalysis by an E2 enzyme that is deeply trapped still contributes strongly to the current when operating at typical conditions (<1 mA/cm 2 ) 56 .…”
Section: The Ranges Of Nadp + /Nadph Cyclingmentioning
confidence: 99%